IMPLEMENTASI KOMUNIKASI KONSELING ISLAMI TERAPIS DALAM PENGEMBANGAN INTERAKSI DAN PERILAKU ANAK PENYANDANG AUTIS MELALUI TERAPI ABA - Sarah Salsabila; Zainun Zainun (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Autism is a developmental disorder, understanding which has an impact on behavior, social interaction, communication and language disorders. Because of these problems, children with autism need to do therapy to improve and reduce existing problems. The early intervention method for dealing with autistic children is using ABA therapy.The purpose of this study was to find out how the implementation of therapist counseling communication in ABA therapy, and how changes in the development of interaction and behavior of autistic children before and after being given ABA therapy. The research design uses descriptive qualitative research. Data collection techniques obtained through observation, interviews, and documentation. From this study it was found that at YPAC Medan the implementation of counseling communication was not implemented. But the implementation of communication is generally done by therapists in the form of interactional communication. Furthermore, there are changes in the development of interaction and communication in autistic children before and after carrying out ABA therapy in that before carrying out ABA therapy children are not at all affected by environmental stimuli, there is no eye contact when communicating and interacting, only focusing on oneself, not responding to external stimuli, and only focus on the object or activity they like. Furthermore, after the child is given ABA therapy, there are visible changes, including starting to be able to respond to stimuli, starting to make eye contact, starting to be able to say words even though they don't understand their meaning and starting to be able to express wishes by giving signs